Model for Developing a Health-Related Quality of Life Questionnaire for Chronic Obstructive Pulmonary Disease - Nikolić Emilija; Nikolić Aleksandar; Stević Ruža; Brandmajer Tijana; Mićanović Veselin; Mašnić Jelena (Canadian Respiratory Journal)
Introduction. The St. George’s Respiratory Questionnaire (SGRQ), Modified Medical Research Council (mMRC) Dyspnea Scale, Hospital Anxiety and Depression Scale (HADS), and general health questionnaire (SF-36) are widely used for chronic respiratory diseases such as chronic obstructive pulmonary disease (COPD). Aim. We examined the reliability and validity of a modified questionnaire (MQ) to create a model for assessing the health-related quality of life (HRQOL) in COPD. Method. In total, 132 COPD patients completed the MQ. Lung function, smoking index, and exacerbation frequency were measured. Cronbach’s α coefficient of correlation, standard deviation, and multifactorial nonlinear regression analysis were used to verify the internal validity of the MQ and to develop the mathematical model. Results. Female (63) patients had lesser airway obstruction than, and exacerbation frequency similar to that of, male patients. Exacerbation frequency significantly correlated with spirometry parameters in female patients. The MQ total score achieved high internal consistency (Cronbach’s α = 0.89) and showed significant correlations with exacerbation frequency, smoking habit, and spirometry parameters in male patients (p<0.005). Conclusion. The HRQOL questionnaire was shown to be a good indicator of the health status of COPD patients. The mathematical model easily and precisely confirmed the score of HRQOL questionnaire.